Analysis of Heterozygous PRKN Variants and Copy‐Number Variations in Parkinson's Disease. Issue 1 (24th September 2020) - Yu, Eric; Rudakou, Uladzislau; Krohn, Lynne; Mufti, Kheireddin; Ruskey, Jennifer A.; Asayesh, Farnaz; Estiar, Mehrdad A.; Spiegelman, Dan; Surface, Matthew; Fahn, Stanley; Waters, Cheryl H.; Greenbaum, Lior; et al.
ABSTRACT: Background: Biallelic PRKN mutation carriers with Parkinson's disease (PD) typically have an earlier disease onset, slow disease progression, and, often, different neuropathology compared to sporadic PD patients. However, the role of heterozygous PRKN variants in the risk of PD is controversial. Objectives: Our aim was to examine the association between heterozygous PRKN variants, including single‐nucleotide variants and copy‐number variations (CNVs), and PD. Methods: We fully sequenced PRKN in 2809 PD patients and 3629 healthy controls, including 1965 late‐onset (63.97 ± 7.79 years, 63% men) and 553 early‐onset PD patients (43.33 ± 6.59 years, 68% men). PRKN was sequenced using targeted next‐generation sequencing with molecular inversion probes. CNVs were identified using a combination of multiplex ligation‐dependent probe amplification and ExomeDepth. To examine whether rare heterozygous single‐nucleotide variants and CNVs in PRKN are associated with PD risk and onset, we used optimized sequence kernel association tests and regression models. Results: We did not find any associations between all types of PRKN variants and risk of PD. Pathogenic and likely‐pathogenic heterozygous single‐nucleotide variants and CNVs were less common among PD patients (1.52%) than among controls (1.8%, false discovery rate‐corrected P = 0.55). No associations with age at onset and in stratified analyses were found. Conclusions: Heterozygous single‐nucleotide variants and CNVs in PRKN are not associated with PD. Molecular inversion probes allow for rapid and cost‐effective detection of all types of PRKN variants, which may be useful for pretrial screening and for clinical and basic science studies targeting specifically PRKN patients. © 2020 International Parkinson and Movement Disorder Society